The Nature of Christian Doctrine: Its Origins, Development, and Function by Alister McGrath, Oxford University Press: Oxford, 2024, 226 pages, hardback £30 (on the OUP website) - Zachhuber, Johannes (New blackfriars, 2026)
The Nature of Christian Doctrine: Its Origins, Development, and Function by Alister McGrath, Oxford University Press: Oxford, 2024, 226 pages, hardback £30 (on the OUP website) - Volume 107 Issue 1